Conserved and nonconserved epitopes among Haemophilus influenzae type b pili. - Gilsdorf, J R (Infect Immun, 1990)
We investigated the binding of antibodies raised against four different Haemophilus influenzae type b (Hib) plus antigen preparations to the native pili and denatured pilins of 21 Hib isolates. Antibodies against live piliated Hib M43p+, adsorbed with a nonpiliated variant to remove nonpilus antibodies, bound to 18 of the 21 piliated Hib isolates in immunodot assays but failed to recognize the denatured pilins from any of the strains in Western immunoblot assays. Similarly, antibodies against purified native pili of strain E1ap+ bound to 11 of 21 piliated strains in immunodot assays but to only 2 of 21 piliated strains in Western blot assays. The native pili of all 21 strains were recognized by one or both of the antisera. These observations suggest that the immunodominant epitopes of native Hib pili are dependent on conformation and are moderately conserved. In contrast, antibodies against denatured M43p+ pilin or against a peptide derived from amino acids 5 through 17 of M43p+ pilin failed to bind to native pili from any of the 21 piliated isolates on immunodot assay. However, both sera recognized the denatured pilins from all the piliated strains on Western blot assay. These data indicate that the immunodominant epitopes of denatured pilins are highly conserved among different strains of Hib but are unavailable on intact pili for antibody binding. IMAGES: